Effects of Sintering Temperature on the Flexural Strength and Shrinkage of Feldspar Reinforced Clay Composite for the Vitrified Clay Pipe Application - Abdul Latif, Noradila; Nur Farah Atiqah Jamaludin; Sharifah Adzila; Joseph Tan; Lim Siak Hooi (International Journal of Integrated Engineering, 2024)
Clay is a common material that was used to manufacture the green sewerage pipe, vitrified clay pipe (VCP). As known, clay is a ceramic material that behaves in a brittle manner. In the current study, addition of appropriate feldspar reinforcement in clay material and heat treatment by sintering method were focused to improve the shrinkage and flexural strength of ceramic clay composite for future material selection in VCP manufacturing at JPC-Intan Sdn. Bhd. Investigation on five different composition ratios between feldspar and clay was conducted. The ratio of clay/feldspar consists of 75/25, 80/20, 85/15, 90/10 and 95/5 (wt%). Subsequently, five different sintering temperatures were subjected to the ceramic clay composite, from 950, 1000, 1050, 1100 and 1120 °C. Shrinkage analysis, flexural test and Scanning Electron Microscopy (SEM) towards fracture surface were performed to the clay and ceramic clay composites. Thermogravimetric Analysis (TGA) and Energy-Dispersive Spectroscopy (EDS) analysis were carried out to the dry clay and fine feldspar powders. Shrinkage of ceramic clay composite apparently temperature dependent. Shrinkage was increased by increasing the sintering temperature for all ceramic clay composites. Flexural strength at sintering temperatures of 1000 °C and above was significantly higher compared to the flexural strength at low sintering temperature of 950 °C for each composition clay/feldspar composite. The highest flexural strength was indicated at ratio of 85/15 at 1100 °C. Plus, all samples were significantly behaved in brittle manner. Pores were obviously seen in fracture surface of clay/feldspar at 950 °C. Meanwhile, pores were reduced at the fracture surface of clay/feldspar composite when sintered at 1100 °C. Less porosity on fracture surface was tended to increase the percentage of shrinkage at high temperature and, also affects the flexural strength with the maximum value achieved.